Tourism for development: A SAM-multiplier study on sports tourism in Kenya - Breisinger, Clemens; Wiebelt, Manfred; Omune, Lensa; Breisinger, Milena; Bordignon, Jacopo (International Food Policy Research Institute, 2025)
Tourism presents a significant, yet largely untapped, opportunity for Africa to accelerate economic development, create jobs, and foster inclusive growth. This case study for sports tourism in Kenya estimates that for every $1,000 spent by a sports tourist, a total of $3,600 is generated within the Kenyan economy, highlighting the sector's substantial linkages with other sectors, particularly the food system. By 2035, sports tourism could contribute an estimated $1.21 billion to $2.14 billion to Kenya's economy annually and support the creation of up to 237,000 new jobs. About half of these jobs are expected to benefit lower and middle-income households, supporting their livelihoods and poverty reduction. To fully realize these economic and social benefits, strategic policy interventions are crucial, including targeted investment in tourism infrastructure, marketing, and skill development; a concerted effort to improve the overall business climate to incentivize private sector engagement; and enhanced inter-ministerial coordination between tourism, planning, agriculture and other key stakeholders. While this study focuses on economic impacts, realizing these benefits requires careful planning and sustainable practices to mitigate potential environmental and social challenges.